Association between the frontoparietal network, clinical symptoms and treatment response in individuals with untreated anorexia nervosa - Qiang Liu; Yan Chen; Zhen Wang; Ling Yue; Hui Zheng; Lei Guo; Jue Chen; Yuping Wang; Qianqian He; Jialin Zhang; Qing Kang; Cheng Lian; et al. (General Psychiatry)
Background Anorexia nervosa (AN) has been characterised as a psychiatric disorder associated with increased control. Currently, it remains difficult to predict treatment response in patients with AN. Their cognitive abilities are known to be resistant to treatment. It has been established that the frontoparietal control network (FPCN) is the direct counterpart of the executive control network. Therefore, the resting-state brain activity of the FPCN may serve as a biomarker to predict treatment response in AN.Aims The study aimed to investigate the association between resting-state functional connectivity (RSFC) of the FPCN, clinical symptoms and treatment response in patients with AN.Methods In this case-control study, 79 female patients with AN and no prior treatment from the Shanghai Mental Health Center and 40 matched healthy controls (HCs) were recruited from January 2015 to March 2022. All participants completed the Questionnaire Version of the Eating Disorder Examination (version 6.0) to assess the severity of their eating disorder symptoms. Additionally, RSFC data were obtained from all participants at baseline by functional magnetic resonance imaging. Patients with AN underwent routine outpatient treatment at the 4th and 12th week, during which time their clinical symptoms were evaluated using the same measures as at baseline.Results Among the 79 patients, 40 completed the 4-week follow-up and 35 completed the 12-week follow-up. The RSFC from the right posterior parietal cortex (PPC) and dorsolateral prefrontal cortex (dlPFC) increased in 79 patients with AN vs 40 HCs after controlling for depression and anxiety symptoms. By multiple linear regression, the RSFC of the PPC to the inferior frontal gyrus was found to be a significant factor for self-reported eating disorder symptoms at baseline and the treatment response to cognitive preoccupations about eating and body image, after controlling for age, age of onset and body mass index. The RSFC in the dlPFC to the middle temporal gyrus and the superior frontal gyrus may be significant factors in the treatment response to binge eating and loss of control/overeating in patients with AN.Conclusions Alterations in RSFC in the FPCN appear to affect self-reported eating disorder symptoms and treatment response in patients with AN. Our findings offer new insight into the pathogenesis of AN and could promote early prevention and treatment.